Implementasi Peraturan Daerah Kota Padang Dalam Mewujudkan Tata Kelola Pemerintahan Yang Transparan Dan Partisipatif - Sarah Georetty Manullang (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the implementation of the Regional Regulation (Perda) of Padang City in promoting transparent and participatory governance. Transparency and public participation are essential principles of good governance, requiring local governments to be open in decision-making processes and to actively involve citizens in public policy formulation. The research adopts a descriptive qualitative approach, utilizing data collection techniques such as document analysis, in-depth interviews with local government officials, and direct observation. The findings indicate that the implementation of Padang City’s regional regulation has provided a legal framework for a more open government, particularly through public information disclosure, community involvement in development planning forums (Musrenbang), and the strengthening of independent oversight institutions. However, several challenges remain in the implementation process, including limited human resource capacity, low public awareness of participatory rights, and the suboptimal use of information technology. Therefore, strong political commitment, enhanced capacity building for government personnel, and continuous public education are needed to ensure that the regulation is effectively implemented and contributes meaningfully to the realization of a transparent, accountable, and participatory local government.